Pemetaan Struktur Peristiwa Bahasa: Komunikasi Bebas Konflik = Mapping structure of speech event: Conflict-free communication - Beden, S.; Zahid, I. (Universiti Kebangsaan Malaysia Press, 2016)
This paper aims to map the structure of language events in the 'Melunas Rindu' novel, a literature text used by students in Form 4 Zone 4 in the states of Johore, Sabah, Sarawak and the Federal Territory of Labuan, Malaysia. The use of literature materials can produce students who think about goodwill, virtues and prioritize politeness. Therefore, such good practice can produce individuals who are proactive in dealing with various situations.Therefore, the politeness aspect needs to be emphasised in oral or written communication in order that no party is offended or is in conflict. In the context of literary writing, language politeness display is manifested through speech events, using certain structures in dialogue in order that the information communicated is conflict-free. The analysis focused on the mapping structure of speech events’ of the main character and a supporting characters’ dialogue in Chapter 16. This study employed a combination of Leech's Model of Politeness (1983) and Grice's Model of Cooperation (1975) which forms the General Maxim Combination Pattern Model (MPKMU) to analyze the research data. This study used library research, text analysis and quantitative method as the instruments. The finding shows that the mapping structures of speech events are varied to fulfil certain requirements for the purpose of creating a situation of conflict free communication. The existence of these situations assure that all sides are in a comfortable zone apart from escalating effectiveness of communication when each speaker’s objectives is achieved. Thus, these situations have manifested the importance of politeness in language. In conclusion, mapping of structure events using the combination of the two models managed to reflect politeness speech events in the 'Melunas Rindu' novel.